Mucormycosis- in a case of diabetes mellitus - Francis, Felin Ann; Shetty, Varun; Khomne, Amit; Ansari, Imran (International Journal of Research in Medical Sciences, 2017)
Mucormycosis is a rare fungal infection seen in immunocompromised people especially with uncontrolled diabetes mellitus – in this case causing orbital cellulitis. Patient of diabetic ketoacidosis was investigated with CT PNS, MRI Brain and Final diagnosis was made after clinical examination, discussion with ENT specialist, ophthalmologist about the best diagnostic technique and an endoscopic nasal biopsy was done - which showed fungal hyphae.